2004
DOI: 10.7326/0003-4819-140-3-200402030-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and Chronic Kidney Disease in U.S. Adults

Abstract: These findings suggest that the metabolic syndrome might be an important factor in the cause of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
717
10
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,200 publications
(795 citation statements)
references
References 22 publications
48
717
10
20
Order By: Relevance
“…Indeed, the frequency of microalbuminuria in the general population has been shown to increase with the degree of obesity. 29 Its frequency was significantly higher in subjects with MS than in those without MS suggesting that in children, as in adults, 30 microalbuminuria is associated with MS. Obese children with MS also had higher concentrations of PAI-1 and uric acid which together with microalbuminuria explained 10.6% of the variance of the MS. This proportion is similar to the 7.4% of the total variance of MS explained by an 'inflammatory factor' in nondiabetic individuals participating in the Insulin Resistance Atherosclerosis Study.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the frequency of microalbuminuria in the general population has been shown to increase with the degree of obesity. 29 Its frequency was significantly higher in subjects with MS than in those without MS suggesting that in children, as in adults, 30 microalbuminuria is associated with MS. Obese children with MS also had higher concentrations of PAI-1 and uric acid which together with microalbuminuria explained 10.6% of the variance of the MS. This proportion is similar to the 7.4% of the total variance of MS explained by an 'inflammatory factor' in nondiabetic individuals participating in the Insulin Resistance Atherosclerosis Study.…”
Section: Discussionmentioning
confidence: 91%
“…15 Obesity is linked to metabolic syndrome, 25 a condition associated with chronic kidney disease. 17 While the presence of metabolic syndrome was not assessed directly, it is plausible that syndrome components (diabetes, hypertension, hyperlipidemia, glucose intolerance, or insulin resistance) may have acted in concert to increase risk, though parsing the relevance of individual factors is challenging. Data from the ACS-NSQIP found that diabetics were 1.3 (for those on oral therapy) to 1.7 (for those on insulin therapy) times more likely to develop postoperative AKI, 16 a degree of increased risk comparable with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Insulin resistance has been reported to increase the risk of CKD. 18,19 Chen et al 18,19 determined that metabolic syndrome 19 and insulin resistance estimated by a homeostasis model assessment 18 were associated with an increased CKD risk in participants in the NHANES III study.…”
Section: Discussionmentioning
confidence: 99%